In-situ solution chemical reaction deposition of Bi2S3 quantum dots on mesoscopic TiO2 films for application in quantum-dot-sensitized solar cells. Issue 169 (12th February 2016) - Ma, Yuanliang; Li, Haiqin; Yuan, Jing
ABSTRACT: Bi2 S3 quantum dots modified mesoscopic TiO2 films were prepared by in-situ solution chemical reaction deposition, using ethylene glycol monomethylether (EGME) and ethanol as solvent of Cationic precursor solution and anionic precursor solution respectively. UV-vis-NIR absorption spectra reveal that the Bi2 S3 QDs extends the range of the photo response of the TiO2 films to visible region. A maximum conversion efficiency of 0.205% was obtained after five deposition cycles under illumination at 1000 W/m 2 . These results indicate that the Bi2 S3 has potential application in the field of QDSSC.